The Effect of Asymmetry Information, Company Size, Profitability, Leverage and Employee Stock Ownership Programs in Earnings Management - Dhiyaa Nabiilah; Murtanto Murtanto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This research aimed to examine the effect of Asymmetry Information, Company Size, Profitability, Leverage and Employee Stock Ownership Programs on Earnings Management. The population used in this research was consumer cyclicals sector companies listed on the Indonesia Stock Exchange (BEI) from 2019 until 2021. Sample was determined by the purposive sampling method. In line with that, there was 57 companies as the sample with 171 observation data. The method of analysis used was multiple regression analysis. Based on the result of testing the hypothesis in this study indicate that Asymmetry Information, Profitability, and Employee Stock Ownership Programs has no effect on earnings management, meanwhile Compnay Size and Leverage has a negative effect on earning management.